Dampak Pandemi Covid-19 dan Strategi Pengembangan Terhadap Desa Wisata Telaga Biru Cigaru Kabupaten Tangerang - Nadya Rechtta Utami; Nining Yuniati; Amiluhur Soeroso (Magister Tourism Study, Faculty of Tourism, Udayana University, 2022)
Cigaru Blue Lake Rural Tourism is located in Cigaru Village, Cisoka Village, approximately 10 kilometers from the Tangerang Regency Government Headquarters. The attraction of this destination is a distinctive culture and lake that has blue water colour, the lake is not a natural tourism but artificial tourism, the destination has become famous and can become a tourist village in the Cisoka area, Tangerang because it has inclusion from the Cigaru Village government. and supervised by the local community and there is authority as the headman. it has problems, first, related to visits in recent times, visits have decreased even if there are no visitors. Second, several facilities were damaged, there was no cost to renovate, thus hampering its development. The method used is a qualitative case study and the technique used is descriptive. The conclusions from this study were concluded based on the formulation of the existing problems and the results were: The impact of the pandemic on the Cigaru Blue Lake Rural Tourism, namely the decrease in tourist visits that occurred resulting in a decrease in the economic level experienced by the people of Cigaru Village, then the CHSE protocol had not been implemented so that the destination has not been able to operate again. In addition, researchers found other problems outside of the impact of the pandemic, namely the ineffectiveness of the concept of a rural tourist in the destination so that the right strategy was needed to draw conclusions in strategic planning, then the development strategy needed in the Cigaru Blue Lake Rural Tourism, namely by implementing CHSE and developing on facilities and activities (Eco-Lodge, Eco-Recreation and Eco-Education) at Cigaru Blue Lake Rural Tourism. Keywords: rural tourism, cigaru blue lake, development strategy, pandemic, covid-19.